Steel Band, Pier Head, Barbados, B.W.I - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2022)
Picture of a nine-man steel pan band playing at Pier Head in Barbados. There’s a label – Ju-c on one of the steel pans. One man is playing maracas accompanying the playing of the steel pan. There is a casuarina tree in the background and a building with the partial label of BUREAU behind the band. At the back of the post card at the top left-hand corner the following is written in pencil: CCD £15. The post card is divided into two sides with the word POST CARD printed separately. At the left-hand side the following is printed: Copyright: Barbados Publicity Committee Printed by Deppo Holland – The Hague.
Landscape, Black & white, 5 1/2 x 3 1/2 inches
Keywords: Drums (Musical instruments); Percussion instruments; Musical instruments; Musicians; Music; Steel pan; Steelband; Steel orchestra